The Role of Social Media in Shaping Transformational Citizenship - Siti Fauziah (International Journal of Students Education, 2024)
Social media has become an integral part of modern life, influencing various aspects including politics and citizenship. Transformational citizenship highlights the importance of individuals’ active participation in social, political, and environmental issues that affect their communities. This research uses a literature review approach to investigate the role of social media in shaping transformational citizenship. Data was collected from various literature sources such as scientific journals, books and popular articles relevant to the research topic. Analysis of the literature shows that social media provides a platform for individuals to participate in public discussions, obtain information, and mobilize support for social change. However, social media use also poses challenges, such as the spread of false information and polarization of opinion, which can hinder the formation of inclusive and sustainable citizenship. In conclusion, this research highlights the importance of understanding the role and impact of social media in shaping transformational citizenship, as well as emphasizing the need for concerted efforts to maximize the positive benefits of social media while addressing the challenges associated with its use.